High-Sensitivity Cardiac Troponin T Variation After Percutaneous Atrial Septal Defect Closure - Contreras, Alejandro Ernesto (2023)
Troponin levels are used to rule in or rule out myocardial injury, with the T and I subunits being the biomarkers of choice. The use of high-sensitivity kits is recommended in clinical practice.1 There are no reference values after percutaneous occlusion of an ostium secundum–type atrial septal defect (ASD). The objective of this study was to describe the values of high-sensitivity cardiac troponin T (hs-cTnT) in a population that received percutaneous treatment for ASD without complications. This observational, prospective, and comparative study of repeated measurements was conducted between August 2020 and November 2022. Patients with ostium secundum–type ASD, dilated right heart chambers, and percutaneous closure of the defect with devices were consecutively included. High-sensitivity cardiac troponin T levels were measured before the intervention and at 6 hours after the end of the procedure. Measurements were performed on a Cobas autoanalyzer using an electrochemiluminescence assay (Roche). Ultrasensitive troponin T was used. The upper reference limit (URL) was 14 pg/mL. The protocol was approved by the Institutional Research Ethics Committee and Research Committee of the Hospital Privado Universitario de Córdoba. Patients and/or their guardians provided written informed consent.